Pemberdayaan Kewirausahaan Ibu-Ibu PKK Melalui Pelatihan Pembuatan Berbagai Olahan Ikan Di Desa Munjung Agung Kabupaten Tegal - Mei Rani Amalia Amalia; Sari Wiyanti; Eva Anggra Yunita (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Munjung Agung Village is one of the villages in Kramat District, Tegal Regency, Central Java Province. The majority of Munjung Agung villagers work as fishermen who rely on fishing products to meet their daily needs. As for the mothers, most of them work as housewives who have no other income while they actually have a lot of time to use to increase their income. The purpose of implementing this community service is to provide entrepreneurial ideas about fish processing that can be carried out by housewives, especially PKK members and motivate them to become entrepreneurs. The method used is to provide hands-on theoretical and practical training regarding processing fish into products that provide more economic benefits.